Maternal belief system regarding independence of children with cerebral palsy among Saudi mothers - Alkhudair, Rayya (2019)
Background: Cerebral palsy is a non-progressive condition that causes neurological disorders, and is one of the main causes of child disability in Saudi Arabia. Different treatment methods are proposed as part of the rehabilitation plans for children with cerebral palsy. These are usually designed to improve the child’s functional skills, so as to develop their independence, as a major goal. Parents have a major role in their children’s rehabilitation programmes, therefore their understanding of their child’s expected abilities and outcomes is essential. In order to understand the parent’s analysis of their child’s development it may be helpful to explore their beliefs. An overview of the existing literature showed that a number of studies investigated parental beliefs regarding the causes and meanings of their children’s disabilities, the unique skills of the professionals, the impact of religion and also their behaviour toward independence. Whilst some studies addressed some parental behaviour towards some aspects of independence, the current study is the first to explore parental beliefs focusing on different aspects of the independence of children with cerebral palsy.